2017
DOI: 10.18869/acadpub.nfsr.4.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physico-Mechanical and Antimicrobial Properties of Gelatin- Carboxymethyl Cellulose Film Containing Essential Oil of Bane (Pistacia atlantica)

Abstract: A B S T R A C TBackground and Objectives: Microbial activity is the main factor in spoiling food products, which not only changes their texture and taste but also causes economic damage and poisoning. The present study aimed to assess the effects of essential oil of Bane (Pistacia atlantica) on physico-mechanical and antimicrobial properties of gelatin-carboxymethyl cellulose film. Materials and Methods:The solutions (4% w/v) of gelatin and CMC (1% w/v) were prepared in deionized water. Then different levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Dong and Wang (2017) reported the effect of CMC-garlic EO on improving the quality of strawberries. Two other studies reported gelatin/CMC films mixed with bane EO (Ranjibar et al, 2017) and chitosan-CMC films mixed with eucalyptus oil (Pandharipande & Katekhaye, 2017). The purpose of this work was to incorporate four common essential oils into two types of CMC and to determine the physico-mechanical properties of the resulting films.…”
Section: Introductionmentioning
confidence: 99%
“…Dong and Wang (2017) reported the effect of CMC-garlic EO on improving the quality of strawberries. Two other studies reported gelatin/CMC films mixed with bane EO (Ranjibar et al, 2017) and chitosan-CMC films mixed with eucalyptus oil (Pandharipande & Katekhaye, 2017). The purpose of this work was to incorporate four common essential oils into two types of CMC and to determine the physico-mechanical properties of the resulting films.…”
Section: Introductionmentioning
confidence: 99%
“…Raeisi et al 2015 stated that CMC coating incorporated with Zataria multiflora and grape seed essential oils were improved sensorial attributes, increased shelf-life, enhanced chemical, and microbial properties of coated rainbow trout fish during cold storage . The data obtained by study Ranjbar et al 2017 showed that gelatin-CMC coating incorporated with Bene (Pistacia atlantica) essential oil showed acceptable antioxidant and sensorial properties in treated chicken fillets. Therefore, it can be used in meat product (Ranjbar and Azizi, 2017).…”
Section: Carboxymethyl Cellulose (Cmc) Films and Coatingsmentioning
confidence: 96%
“…The data obtained by study Ranjbar et al 2017 showed that gelatin-CMC coating incorporated with Bene (Pistacia atlantica) essential oil showed acceptable antioxidant and sensorial properties in treated chicken fillets. Therefore, it can be used in meat product (Ranjbar and Azizi, 2017).…”
Section: Carboxymethyl Cellulose (Cmc) Films and Coatingsmentioning
confidence: 96%
“…Incorporation of plant extracts, especially essential oils, is an approach for transferring antimicrobial activity to packaging materials (8). Various formulation bases and food stuffs have been studied for this purpose, including alginate-based coating with oregano and rosemary essential oil for coating beef steaks (9), gelatin incorporated essential oils of Pistacia atlantica for coating fillets (10), curcumin loaded nanoemulsions/pectin for coating refrigerated chickens (11), and meat coating with gelatin and henna aqueous extracts (12). Eggs are susceptible to contamination by various microorganisms such as S. enteritidis and S. aureus (13).…”
Section: Introductionmentioning
confidence: 99%